Islamic state as a legal order: to have no law but Islam, between Shari'a and globalization - Ramaioli, Federico Lorenzo (Routledge, 2022)
"This book explores the legal dimension of the Islamic State, an aspect which has hitherto been neglected in the literature. ISIS' dystopian experience, intended as a short-lived territorial and political governance, has been analyzed from multiple points of view, including the geopolitical, social and religious ones. However, its legal dimension has never been properly dealt with in a comprehensive way, assuming as a point of reference both the Islamic and the Western legal tradition. This book analyzes ISIS as the expression of a potential though never fully realized legal order. The book does not describe ISIS' possible classifications according to the standards and the criteria of international law, such as its possible statehood or proto-statehood, issues that are however touched upon. Rather, it analyzes ISIS' own legal awareness, based on the group's literary materials, which show a considerable amount of juridical work. Such material, mainly propagandistic in its nature, is essential in understanding which kind of legal order ISIS aimed at establishing. The book will be of interest to students and academics in the fields of Law, International Relations, Political Sciences, Terrorism Studies, Religion and Middle Eastern Studies"--